Mindfulness and Its Relationship With cognitive motivation Among University Students - Natik Fahal Al-Kubaisy, (International Journal of Psychosocial Rehabilitation, 2025)
In recent years, some topics which are classified within the Cognitive Behavior Therapy (CBT) on the deployment of mindful awareness in a reflexive, any individual usually learn to distinguish ideas and agitation that help to adapt the ideas and agitation not successful adjustment assistance. The study recommended the preparation of behavioral programs, knowledge of specialists in the fields of psychological and educational institutions to work to diagnose the problems and limitation of students and raise the level of personal efficiency have increased confidence in order to raise the case of cognitive motivation have recommended that increased attention to raising the level of scientific knowledge and the development of motivated students based on scientific principles and methodology. A study of the correlation between the concept of Mindfullness and its relationship with other cognitive styles, as well as relational study on the relationship of the cognitive motive other variables not studied by current research.